Improvement of Credit Processing Model of Commercial Banks on the Scale Scale System - Norov Akmal Ruzimamatovich (International Journal on Orange Technologies, 2022)
The article describes a new model of compliance with the terms of credit of business entities by commercial banks and its evaluation. In this regard, the advantages of the "system of transformation of lending practices" scoring system, developed by combining national and foreign experience, are highlighted.